IMPORTANCE OF USING ICT IN TEACHING LISTENING SKILLS AT SCHOOLS - Abdurazzoqova Sabohat Abdurazzoq qizi; Ergasheva Makhfuza Sohib qizi (PEDAGOGS, 2024)
Abstract: This article discusses the importance of using ICT for teaching listening skills at schools effectively. In the article there are given advantages of ICT while teaching listening for school children.